Impact of Frailty and Malnutrition on Outcomes After Surgical Fixation of Lower Extremity Fractures in Young Patients. Issue 4 (April 2021) - Phen, Huai Ming; Jones, Corey; Kravets, Victoria G.; Farley, Kevin Xavier; Schwartz, Andrew M.; Wilson, Jacob M.; Schenker, Mara L.
Abstract : Objectives: Evaluate the relationship of nutrition parameters and the modified frailty index (mFI) on postsurgical complications within a young patient population sustaining lower extremity orthopaedic trauma. Design: Retrospective observational cohort study. Setting: Urban, American College of Surgeons-Verified, Level-1, Trauma Center. Patients/Participants: Seventeen-thousand one hundred nine adult patients under the age of 65 sustaining lower extremity fractures undergoing operative intervention from 2006 to 2018. Main Outcome Measures: On admission, mFI and albumin levels were obtained, as well as complication data. Statistical analysis was used to analyze the association between frailty, malnutrition, and postoperative complications. Patients were stratified, healthy (mFI ⩽1, albumin ≥3.5 g/dL), malnourished (mFI ⩽1, albumin <3.5 g/dL), frail (mFI ≥2, albumin ≥3.5 g/dL), and frail and malnourished (mFI ≥2, albumin <3.5 g/dL). Results: 60.4% of patients were healthy, 18.8% were malnourished, 11.7% were frail, and 9.0% were frail and malnourished. Frailty and/or malnourishment on admission predicted significantly higher odds of postoperative complications and mortality when compared with healthy patients. Frailty and malnourishment in conjunction predicted a significantly higher odds ratio of 1.46 (1.22–1.75) for developing postoperative complications when compared with the only malnourished. This was also observed when compared with the only frail (odd ratio: 1.61, P < 0.001); however, there was also a 2.72 ( P < 0.001) increased odds of mortality. Conclusions: Frailty and malnutrition in conjunction predicts a subset of patients with a higher risk of postoperative complications beyond that of frailty or malnutrition in isolation. Identification of these physiological states on admission allows for interventional opportunities during hospitalization. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.